A evolução de materiais na indústria automobilística : o caso Volkswagen caminhões e ônibus - Alves, Manuela Fontana (2006)
The present work has its focus on the innovation of materials in the automobile industries; more specifically for commercial vehicles and attempts to show which changes has occurred in the past 20 years and its result for the environmental impact. With these propose and by utilizing the concept of Life Cycle Assessment, a comparative study between an old and a new project for cab will be done. At this study it will be take in account the following stages of a product life cycle: production, maintenance and final disposal. By getting all different materials which the cab is made and its relation with the total weight for the cab it will be possible to identify the process of material substitution that has been occurring in automobilist industries and its relation at the increasingly environmental worrying.